The Recovery in the Public Finances in Ireland following the Financial Crisis - Smyth, Diarmuid (SSISI, 2017)
The turnaround in the fiscal position in Ireland over the past 6-7 years has been dramatic. From double-digit deficits, a rapidly rising debt ratio and entry into an EU/IMF support programme, by end 2015, the General Government deficit and debt ratios were down to 1.9 and 78.6 per cent of GDP, respectively – the latter falling by 40 percentage points in 3 years. This culminated in a successful exit from both the programme and the Excessive Deficit Procedure (EDP). Much of this progress reflects the hard choices made (beginning in 2008) to correct the public finances through a series of consolidation measures totalling €30 billion. The key role played by interest costs in facilitating this turnaround is however often overlooked as are a number of other well timed factors including data revisions and stronger than expected revenues. This paper takes a comprehensive look back at these factors and their roles in facilitating the exit from the EDP while also enabling higher levels of spending.
read before the Society, 25 May 2017
Keywords: crisis management; debt; Ireland; 314.15